Golden memories - Shannon, Clara M. Sainsbury, 1858-1930.; Prentiss, Richard St. John.
Memoir written by Shannon relating to her service as a member of Mary Baker Eddy's household (1894-1903). Edited with a forward (1975) by Richard St. John Prentiss.
Typewritten transcript.
Christian Scientist and religious worker.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Eddy, Mary Baker, -- 1821-1910.; Christian Science; Religious workers